2016
DOI: 10.1007/s00221-016-4746-x
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal activity decline in women under a single dose of diazepam during rule-guided responses: an fMRI study

Abstract: Daily life events confront us with new situations demanding responses to usual and unusual rules. Diazepam (DZ), a clinically important drug, facilitates the inhibitory activity of the GABAergic system. Prefrontal cortex, rich in DZ receptors, coordinates necessary resources to direct actions according to rules. The balance between excitatory and inhibitory activity is critical to achieve optimal function of brain systems leading to complex functions. Major sex differences in the physiological mechanisms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
2
1
0
Order By: Relevance
“…In contrast to the Flanker task, response times in the SST did not depend on gambling status, but the positive correlations between Go error response times and dACC GABA+/Cr and the GABA+/Glx ratio indicated GD-specific abnormalities. Previous research with non-gambling populations showed that enhancing GABA levels via agonists, such as Diazepam or Lorazepam, prolongs response times across tasks 38,68 , like the positive association between baseline GABA+/Cr and SST response times found in the current investigation. While GABA agonists induce widespread increases in cortical GABA, our investigation found the relationship between GABA+/Cr and response times significant within the dACC voxel.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast to the Flanker task, response times in the SST did not depend on gambling status, but the positive correlations between Go error response times and dACC GABA+/Cr and the GABA+/Glx ratio indicated GD-specific abnormalities. Previous research with non-gambling populations showed that enhancing GABA levels via agonists, such as Diazepam or Lorazepam, prolongs response times across tasks 38,68 , like the positive association between baseline GABA+/Cr and SST response times found in the current investigation. While GABA agonists induce widespread increases in cortical GABA, our investigation found the relationship between GABA+/Cr and response times significant within the dACC voxel.…”
Section: Discussionsupporting
confidence: 77%
“…Tan et al obtained comparable results in the mPFC of females after chronic adolescent social isolation stress, with pyramidal neurons being less activated during sociability tests [ 39 ]. Alprazolam significantly lowered the number of cFos+ cells in the IL compared to vehicle-injected female controls, consistent with the benzodiazepine effects observed in humans: women demonstrate decreased activity in frontal regions after treatment, while an opposite effect is present in males [ 40 ]. This effect could be related to females having significantly higher GABA-A benzodiazepine receptor availability [ 41 ].…”
Section: Discussionsupporting
confidence: 68%
“…Sex differences in the modulation of social behavior by the mPFC were previously explored regarding oxytocin-receptor-expressing interneurons which have differential responses to oxytocin in male and female mice and regulate the social motivation of female mice to interact with male mice during estrus [37]. Alprazolam significantly lowered the number of cFos+ cells in the IL compared to vehicle-injected female controls, consistent with the benzodiazepine effects observed in humans: women demonstrate decreased activity in frontal regions after treatment, while an opposite effect is present in males [38]. This effect could be related to females having significantly higher GABA-A benzodiazepine receptor availability [39].…”
Section: Discussionmentioning
confidence: 72%